In Vitro Modulation of P-Glycoprotein Activity by Euphorbia intisy Essential Oil on Acute Myeloid Leukemia Cell Line HL-60R - Paola Poma; Manuela Labbozzetta; Aro Vonjy Ramarosandratana; Sergio Rosselli; Marco Tutone; Maurizio Sajeva; Monica Notarbartolo (Pharmaceuticals, 2021)
Euphorbia species have a large spectrum of traditional medicinal uses. We tested the biological activities of the essential oil (EO) of Euphorbia intisy Drake in an acquired multidrug resistance leukemia model to assess whether the EO obtained by hydrodistillation of stems was able to reverse the resistant phenotype. HL-60R cell lines are characterized by the overexpression of P-glycoprotein (P-gp), inhibitors of apoptosis proteins (IAPs) and constitutive expression of NF-κB. EO chemical composition was determined by GC/MS analysis; cytotoxic activity of EO by MTS assay alone or in combination with doxorubicin; pro-apoptotic effect and doxorubicin accumulation were analyzed by flow cytometry; P-gp ATPase activity was measured by P-gp-Glo™ assay systems kit. The ability to inhibit NF-κB and its target genes was also assessed. E. intisy EO exhibited a comparable cytotoxic effect and ability to block P-gp in both the HL-60 and its MDR variant HL-60R. In addition, EO suppressed P-gp protein expression and significantly downregulated MDR1 mRNA level, as well as some IAPs proteins, probably through the inhibition of NF-κB. Our results suggest that E. intisy EO could reverse P-gp-mediated drug resistance in tumor cells acting as a chemosensitizing agent.